Effects of Virtual Human Appearance Fidelity on Emotion Contagion in Affective Inter-Personal Simulations - Volonte, Matias; Babu, Sabarish V.; Chaturvedi, Himanshu; Newsome, Nathan; Ebrahimi, Elham; Roy, Tania; Daily, Shaundra B.; Fasolino, Tracy (IEEE transactions on visualization and computer graphics, 2016)
Realistic versus stylized depictions of virtual humans in simulated inter-personal situations and their ability to elicit emotional responses in users has been an open question for artists and researchers alike. We empirically evaluated the effects of near visually realistic vs. non-realistic stylized appearance of virtual humans on the emotional response of participants in a medical virtual reality system that was designed to educate users in recognizing the signs and symptoms of patient deterioration. In a between-subjects experiment protocol, participants interacted with one of three different appearances of a virtual patient, namely visually realistic, cartoon-shaded and charcoal-sketch like conditions in a mixed reality simulation. Emotional impact were measured via a combination of quantitative objective measures were gathered using skin Electrodermal Activity (EDA) sensors, and quantitative subjective measures such as the Differential Emotion Survey (DES IV), Positive and Negative Affect Schedule (PANAS), and Social Presence questionnaire. The emotional states of the participants were analyzed across four distinct time steps during which the medical condition of the virtual patient deteriorated (an emotionally stressful interaction), and were contrasted to a baseline affective state. Objective EDA results showed that in all three conditions, male participants exhibited greater levels of arousal as compared to female participants. We found that negative affect levels were significantly lower in the visually realistic condition, as compared to the stylized appearance conditions. Furthermore, in emotional dimensions of interest-excitement, surprise, anger, fear and guilt participants in all conditions responded similarly. However, in social emotional constructs of shyness, presence, perceived personality, and enjoyment-joy, we found that participants responded differently in the visually realistic condition as compared to the cartoon and sketch conditions. Our study suggests that virtual human appearance can affect not only critical emotional reactions in affective inter-oersonal trainina scenarios. but also users' oerceotions of oersonalitv and social characteristic of the virtual interlocutors.